Strategy Of China's Political Economy In The Era Of Deng Xiaoping In China To Build Economic Growth - Akiki Q Sihotang (Institute of Computer Science (IOCS), 2020)
This study aims to determine the strategy of China's political economy in the era of Deng Xiaoping in China to build economic growth. Political economic strategy in question is related to the economic and political policies were implemented by the Chinese state in promoting economic growth of the country. In this case Deng Xiaoping as the pioneer of Chinese economic turnaround, do some political economic strategies showcased in Economic Reform policy at the plenary session of the third meeting of the Central Committee of the Communist Party of China in December 1978. Theory used to describe the problem of this research is the theory of strategy, Paradigm and Political Economic System, Economic System Liberal Capitalist, Socialism and Communist (Radical Political Economy). In this study the authors used the method of writing the kind of descriptive writing with qualitative research. In writing this study the authors use secondary data obtained from the secondary data obtained from the literature and is written using deductive writing techniques. Results of this study indicate that the political economic strategy adopted Deng Xiaoping in building China 's economic growth is not done in a totalitarian economic and political structures, but in a way that carefully and gradually, it is done to see the effect of economic policy on economic growth. Political economic strategy is first applied to Deng Xiaoping's policy is to issue a removal of people's communes, both removal of state monopolies, opening up a third of the foreign capital, business and management liberalization fourth, fifth in international economic integration. This economic strategy eventually reapgreat result. The impact of the economic success of the strategy is then to change the political culture of the Chinese economy towards socialism communist capitalism.